Formation of the Legionella Replicative Compartment at the Crossroads of Retrograde Trafficking - Bärlocher, Kevin; Welin, Amanda; Hilbi, Hubert (Frontiers in Cellular and Infection Microbiology, 2017)
Retrograde trafficking from the endosomal system through the Golgi apparatus back to the endoplasmic reticulum is an essential pathway in eukaryotic cells, serving to maintain organelle identity and to recycle empty cargo receptors delivered by the secretory pathway. Intracellular replication of several bacterial pathogens, including Legionella pneumophila, is restricted by the retrograde trafficking pathway. L. pneumophila employs the Icm/Dot type IV secretion system (T4SS) to form the replication-permissive Legionella-containing vacuole (LCV), which is decorated with multiple components of the retrograde trafficking machinery as well as retrograde cargo receptors. The L. pneumophila effector protein RidL is secreted by the T4SS and interferes with retrograde trafficking. Here, we review recent evidence that the LCV interacts with the retrograde trafficking pathway, discuss the possible sites of action and function of RidL in the retrograde route, and put forth the hypothesis that the LCV is an acceptor compartment of retrograde transport vesicles.